Rheological properties of transglutaminase-treated concentrated pea protein under conditions relevant to high-moisture extrusion processing - Qin, Jianxin; Zhao, Yinghan; Zhou, Jingwen; Zhang, Guoqiang; Li, Jianghua; Liu, Xiao (Frontiers in Nutrition, 2022)
At present, the structural changes of extruded materials under thermal-mechanical stress during high-moisture extrusion are still unclear. In this study, the transglutaminase (TG) treatments on the structure of pea protein isolate (PPI) under conditions relevant to high-moisture extrusion processing (50 wt% PPI at 30 °C, 120 °C and heated to 120 °C and subsequently cooled to 30 °C) was studied by using a closed cavity rheometer. Strain and frequency sweeping were carried out under various temperature conditions, and the information obtained was drawn into a texture map. Lissajous curves combined with energy dissipation ratio were introduced to characterize the nonlinear response of the samples. The results showed that the storage modulus of PPI increased with the increase of TG concentration during heat treatment. After cooling to 30 °C, PPI with 0.25-1%TG could enhance the elasticity, but treating by 2% TG could inhibit the formation of disulfide bonds, the uniform development of the protein network, thus showing the “tough” character. These findings can help to better understand the relationships of material-structure during the extrusion process, and also provides help for further optimization of the quality of meat substitutes.